Ethical Critique of Polygamy in the Early 20ᵗʰ Century Javanese Manuscript Alakirabi Wayuh Kaliyan Botên - Zulaili, Iin Nur; Muhammad Khodafi; Muchamad Saiful Muluk; Nafi, Moh. Iqbal; Ahmad Nabil Nasyiri (Jurnal Lektur Keagamaan, 2025)
This study examines domestic ethics and moral reflections on polygamy in the early twentieth‑century Javanese piwulang manuscript Alakirabi Wayuh Kaliyan Botên (AWKB). Previous research on Javanese household teachings has predominantly emphasized women’s duties and obedience, leaving the moral responsibilities of husbands and the ethical consequences of polygamy largely unaddressed. This study fills that gap by analyzing AWKB as a rare textual source that articulates internal criticism of polygamy within the Javanese intellectual tradition. The research uses a descriptive analytical method based on philological data sourced from the digitized AWKB manuscript written in Javanese script and language. The manuscript was transliterated, paraphrased, and translated, followed by interpretive analysis using Paul Ricoeur’s hermeneutic framework to contextualize its ethical messages. The findings show three key insights. First, AWKB presents implicit criticism of polygamy by highlighting the husband’s inability to maintain material and emotional justice among wives. Second, the text emphasizes maturity, economic preparedness, and honesty as essential foundations for marital stability. Third, AWKB reframes domestic ethics by shifting moral responsibility from women’s obedience toward the husband’s ethical accountability. These findings contribute to Javanese philological studies by revealing an understudied moral discourse that challenges normative assumptions about gender roles in traditional household teachings. The study concludes that AWKB offers a culturally grounded critique of polygamy and provides a valuable ethical perspective for contemporary discussions on marital justice and family well‑being.